2012
DOI: 10.1002/masy.201250309
|View full text |Cite
|
Sign up to set email alerts
|

Vinyl Monomers, Polymers and Supramolecular Assemblies from Aminocaprolactam

Abstract: Summary: a-Aminocaprolactam is a ''green'' monomer in two ways: it is a fermentation product from sugars, and its derivatives are naturally biocompatible and biodegradable. In this overview, the synthesis of a variety of a-amino-e-caprolactam (ACL) derivatives through reaction with acid chlorides, anhydrides, and alkyl halides is described first. The product vinyl and divinyl derivatives were then polymerized using free radical initiators, and the obtained polymers characterized by solution NMR spectroscopy, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Racemic α-amino-ε-caprolactam ( 2 ) was obtained according to literature via cyclocondensation of L-lysine ( 1 ) [ 15 ]. Through amidation of the primary amine ( 2 ) with methacryloyl chloride ( 3 ) the polymerizable 2-methacrylamido-caprolactam ( 4 ) was obtained ( Scheme 1 ) [ 14 ]. Free radical copolymerization of 4 in various comonomer compositions with N , N -dimethylacrylamide ( 5 ) leads to copolymers 6a–i ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Racemic α-amino-ε-caprolactam ( 2 ) was obtained according to literature via cyclocondensation of L-lysine ( 1 ) [ 15 ]. Through amidation of the primary amine ( 2 ) with methacryloyl chloride ( 3 ) the polymerizable 2-methacrylamido-caprolactam ( 4 ) was obtained ( Scheme 1 ) [ 14 ]. Free radical copolymerization of 4 in various comonomer compositions with N , N -dimethylacrylamide ( 5 ) leads to copolymers 6a–i ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study we evaluate the thermoresponsive behavior of solutions of polymers containing 2-methacrylamido-caprolactam as a comonomer. The used α-amino-ε-caprolactam is obtained from biomass through a combination of biological fermentation and chemical processes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,1 0 -carbonyl-bis-caprolactam, as chain extender, improving in particular the strain at break of PA6 [29,30]. Recently, Mathias and co-workers proposed the synthesis of vinyl monomers from a-amino-ε-caprolactam for the preparation of new vinyl polymers and supramolecular assemblies [31]. The shortage of examples arises from the difficulties to synthesize new ε-caprolactam derivatives monomers which are generally obtained by rather complex and time consuming procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Vinyl and divinyl derivatives of natural l ‐lysine‐based α ‐aminocaprolactam as well as bis‐ and tetracaprolactams were reported earlier . In these publications, surprisingly high glass transition temperatures ( T g ) and self‐association of the polycaprolactams due to formation of hydrogen bonds were reported.…”
Section: Introductionmentioning
confidence: 95%
“…18 Vinyl and divinyl derivatives of natural L-lysine-based -aminocaprolactam as well as bis-and tetracaprolactams were reported earlier. 19,20 In these publications, surprisingly high glass transition temperatures (T g ) and self-association of the polycaprolactams due to formation of hydrogen bonds were reported. Recently, we showed that solutions of poly(meth)acrylamide copolymers bearing -aminocaprolactam moieties directly attached to the backbone can change the thermo-responsive behaviour from LCST to UCST by variation of the solvent from water to alcohol.…”
Section: Introductionmentioning
confidence: 99%